Biogenic coal-to-methane conversion can be enhanced with small additions of algal amendment in field-relevant upflow column reactors. (15th November 2019) - Davis, Katherine J.; Platt, George A.; Barnhart, Elliott P.; Hiebert, Randy; Hyatt, Robert; Fields, Matthew W.; Gerlach, Robin
Highlights: Algal amendment increased biogenic coal-to-methane conversion. Produced gas exceeded full conversion of amendment, indicating coal-to-CH4 conversion. 13 C analysis indicated <4% of amendment was converted to measurable gases. A larger fraction of CO2 sorbed to coal than did CH4 . Continuous flow reactors appear to overcome some limitations of coal batch reactors. Abstract: Subsurface coal environments, where biogenic coal-to-methane conversion occurs, are difficult to access, resulting in inherent challenges and expenses for in situ experiments. Previous batch reactor studies provided insights into specific processes, pathways, kinetics, and engineering strategies, but field-relevance is restricted due to limited substrate availability or byproduct accumulation that may influence reactions or metabolisms. In this study, continuous-flow column reactors were used to overcome some batch limitations, improve the understanding of in situ conditions, and increase field-relevance for subsurface engineering technology development. The bench-scale reactor system was constructed to investigate the addition of algal amendment for enhancing microbial coal-to-methane conversion previously developed in batch systems. Four reactor columns were packed with coal and inoculated with a microbial consortium from the same Flowers-Goodale coal bed. Two reactors were amended with 13 C-labeled algal amendment on day 0, and two were unamended. On day 61, one previously amended and one previously unamended reactor were re-amended. Produced gases were captured in a gas trap, and CH4 and CO2 were quantified. The reactor amended twice produced 1712.6 µmol CH4 (4.6% as 13 CH4 ). The reactor amended only on day 0 produced 1485.5 µmol CH4 (2.6% as 13 CH4 ). The reactor amended only on day 61 produced 278.9 µmol CH4 (3.9% as 13 CH4 ). The reactor with no amendment produced no measurable gases for the duration of the 172-day experiment. Amendment increased the rate of coal-to-methane conversion and total gas production; most of the produced gases were due to coal conversion with only small contributions (<7%) from amendment conversion.